Clinical Management of Root Resorption: A Report of Three Cases - Mehra, Neha (Cureus, 2018)
Root resorption is a pathological condition that may be an endodontic challenge if not diagnosed and treated correctly. The recent advances in the imaging technologies and material science have enabled the clinician to visualize the structural changes accurately and repair them with materials providing favourable seal ability. In this article, we report three cases of root resorption with different presentations which were diagnosed with the help of cone beam computed tomography (CBCT) and successfully managed. The series highlights the importance of diagnosis in unusual clinical situations and recommends early commencement of optimal management for longevity of tooth for health and function.